2018
DOI: 10.21273/horttech04180-18
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Methods of Transplanting Pecan Trees

Abstract: When trees with taproots are grown in containers, the taproot typically spirals around the bottom of the container. Currently, there is no consensus on what is the best thing to do about it. Pecan (Carya illinoinensis) grafted container-grown trees were transplanted under three treatment conditions. The treatments were container trees 1) planted straight from the container with no root pruning and no disturbance, 2) planted with taproots pruned so they no longer curled around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…illinoinensis. Ouedraogo et al (2018) found pruning of circling taproots of containergrown C. illinoinensis did not influence stem caliper or shoot growth 4 years after transplanting. Albeit the plants were younger and evaluated within 1 year, the results of our experiment with five different species of Carya corroborate this theme.…”
Section: Discussionmentioning
confidence: 84%
“…illinoinensis. Ouedraogo et al (2018) found pruning of circling taproots of containergrown C. illinoinensis did not influence stem caliper or shoot growth 4 years after transplanting. Albeit the plants were younger and evaluated within 1 year, the results of our experiment with five different species of Carya corroborate this theme.…”
Section: Discussionmentioning
confidence: 84%